Газар доорхи усны тэжээмжийг усны түвшний хэлбэлзлээр тооцсон үр дүн (Ундайн голын жишээн дээр) - Д. Алтантунгалаг (Geological Issues, 2023)
The temporal distribution of recharge in shallow aquifer along the river bed of Undai gol was investigated by water table fluctuation method using precipitation, water-level data. In this study, we have synthesized three-year data derived from the monitoring studies as well field measurements. Recharge was calculated using Schict and Walton (1961) equation. Specific yield was selected as 0.2 due to local lithology of the water bearing rock; Δh was estimated based on the master cumulative decline graph, which was modified from the fluctuation trend of water table during the certain period. The actual water rises were measured, whereas the potential groundwater declines were calculated by equation (2). The main results are (1) the variation of groundwater recharge related to diurnal or seasonal intervals precipitation changes. (2) the water table quickly rises in response to recharge in the shallow aquifer. (3) the peak of ground water recharge was observed 30.76 centimeters in August, 2015 overlap to the maximum value of precipitation in the period. Unconfined aquifer in the study area was recharged only summer season.